Hematological and biochemical markers and cytokine levels in hospitalized psychiatric patients with COVID-19 - Dai, Huirong; Chang, Chih-Jung; Li, Zishun; Liu, Farong; Zhang, Qiao; Bai, Yixuan; You, Pan (Frontiers in Immunology, 2025)
BackgroundMultiple lines of evidence indicate a connection between the pathogenesis of coronavirus disease 2019 (COVID-19) and psychiatric diseases (PDs). To improve the treatment and management of individuals with psychosis and COVID-19, we evaluated biomarkers of PD patients, including those with schizophrenia (SCZ), bipolar disorder (BD), and major depression (MDD), along with the biomarkers of COVID-19.MethodsIn this study, 104 inpatients with concurrent PD and COVID-19 (PD+), the same 104 PD patients after they had recovered from COVID-19 (PD-), and 97 healthy controls (HCs) were evaluated. We analyzed the peripheral blood hematological parameters, serum biochemical parameters, and cytokine levels of the participants and compared the results among the three groups.ResultsThe monocyte count; neutrophil-to-lymphocyte ratio (NLR); monocyte-to-lymphocyte ratio (MLR); systemic immune-inflammation index (SII); and C-reactive protein (CRP), serum CK isoenzyme MB (CK-MB), glucose (GLU), and interleukin (IL)-6 levels were significantly greater (P < 0.05), whereas the magnesium (Mg) level was lower (P < 0.05) in both the PD+ and PD- groups than in the HC group. Moreover, the above indicators were significantly different between the PD+ and PD- groups (P < 0.05).ConclusionNeutrophil count, monocyte count, NLR, MLR, SII, CRP, CK-MB, GLU and IL-6 levels were positively correlated with COVID-19 and PD. The Mg level was negatively correlated with COVID-19 and PD. Our findings suggest that Mg supplementation might be considered a potential treatment approach for PD patients with COVID-19. Despite these insights, the underlying pathophysiological mechanisms remain unclear, highlighting the vital need for further research to validate and build upon these findings.